Enhanced Time Quantum based Round Robin Algorithm for Cloudlet Scheduling in Cloud Environment - et. al., D.Gritto, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The contemporary organization integrates most of the required resources into their business environment by adopting or leasing the cloud resources that are offered by many of the remote cloud service providers. The cloud computing renders hassle free installation, deployment and maintenance of the resources. The cloud resources and services are observed to be pervasive in nature and therefore efficient technologies are to be adopted in order ensure the effective resource utilization and optimal service delivery to the cloud users. Generally virtualization, optimal scheduling techniques like cloudlet scheduling, virtual machine scheduling and load balancing strategies maximize the resource utilization and service delivery. This paper outlines the foundation concepts of cloud computing and proposes an algorithm named Enhanced Time Quantum based Round Robin Algorithm (ETQRRA). The ETQRRA is proposed to reduce the response time, waiting time, turnaround time and the number of context switching. The result of ETQRRA algorithm is compared with various versions of the existing Round Robin algorithms like Classic Round Robin Algorithm (CRR), Improved Shortest Remaining Burst Round Robin (ISRBRR), Half Life Variable Quantum Time Round Robin (HLVQTRR), Improved Round Robin Varying Quantum (IRRVQ) and Dynamic Time Quantum Round Robin (DTQRR) algorithms to prove the efficiency of ETQRRA. The comparative study shows the performance of ETQRRA outdo the other algorithms taken for the comparison.